A CO Adsorption Site Change Induced by Copper Substitution in a Ruthenium Catalyst for Enhanced CO Oxidation Activity. Issue 8 (27th December 2018) - Huang, Bo; Kobayashi, Hirokazu; Yamamoto, Tomokazu; Toriyama, Takaaki; Matsumura, Syo; Nishida, Yoshihide; Sato, Katsutoshi; Nagaoka, Katsutoshi; Haneda, Masaaki; Xie, Wei; Nanba, Yusuke; Koyama, Michihisa; et al.
Abstract: Ru is an important catalyst in many types of reactions. Specifically, Ru is well known as the best monometallic catalyst for oxidation of carbon monoxide (CO) and has been practically used in residential fuel cell systems. However, Ru is a minor metal, and the supply risk often causes violent fluctuations in the price of Ru. Performance‐improved and cost‐reduced solid‐solution alloy nanoparticles of the Cu‐Ru system for CO oxidation are now presented. Over the whole composition range, all of the Cu x Ru1− x nanoparticles exhibit significantly enhanced CO oxidation activities, even at 70 at % of inexpensive Cu, compared to Ru nanoparticles. Only 5 at % replacement of Ru with Cu provided much better CO oxidation activity, and the maximum activity was achieved by 20 at % replacement of Ru by Cu. The origin of the high catalytic performance was found as CO site change by Cu substitution, which was investigated using in situ Fourier transform infrared spectra and theoretical calculations. Abstract : Copper helps out : The weakening of the CO adsorption energy on Ru atoms by alloying with Cu atoms plays an important role in the enhancement of the CO oxidation activity of Cux Ru1− x nanoparticles. The weakening of the CO adsorption energy on Ru atoms originating from the CO adsorption site change was confirmed by experimental and theoretical investigations.